Using simulation to analyze the maintenance architecture for a USAF weapon system. (March 2013) - Garza, Ricardo; Hill, Raymond R; Mattioda, Daniel D
The United States Air Force (USAF) is investigating the use of three levels of repair with its aircraft maintenance managerial structure. This study provides an initial look at the effect of maintenance resource collaboration among maintenance locations and the use of a centralized repair facility focusing on a critical line replacement unit for a major USAF weapon system. Maintenance data for prior year maintenance experiences are collected, fit into appropriate probability distributions and implemented in a discrete event simulation model. This model is then used within an experimental design framework to examine the potential impact of organizational changes to the USAF hierarchical maintenance structure.